The inhibitory effect of copper, zinc, and manganese on Legionella longbeachae and other Legionella spp. in vitro - Jun, Hyunwoo; Scott-Thomas, Amy; Slow, Sandy; Williman, Jonathan; Murdoch, David R; Chambers, Stephen T (Letters in applied microbiology, 2023)
Legionella longbeachae is an important cause of Legionnaires’ disease in Australasia and is associated with exposure to potting soils. Our aim was to identify ways to reduce the load of L. longbeachae in potting soils. Inductively-coupled plasma optical emission spectrometry (ICP-OES) of an all-purpose potting mix showed copper (Cu) concentrations (mg/kg) range from 15.8 to 23.6. Zinc (Zn) and manganese (Mn) were significantly higher than Cu ranging from 88.6–106 to 171–203, respectively. Minimal inhibitory and bactericidal concentrations of 10 salts used in the horticultural industry were determined for Legionella species in buffered yeast extract (BYE) broth. For L. longbeachae (n = 9) the median (range) minimum inhibitory concentration (MIC) (mg/L) of copper sulfate was 31.25 (15.6–31.25), zinc sulfate 31.25 (7.81–31.25), and manganese sulfate 31.25 (7.81–62.5). The MIC and minimum bactericidal concentration (MBC) were within one dilution of each other. Susceptibility to Cu and Zn salts increased as the concentration of pyrophosphate iron in the media decreased. The MIC values for these three metals against Legionella pneumophila (n = 3) and Legionella micdadei (n = 4) were similar. Combinations of Cu, Zn, and Mn were additive. Legionella longbeachae has similar susceptibility to Cu and other metal ions in comparison to L. pneumophila.